2018
DOI: 10.3389/fmicb.2018.00514
|View full text |Cite
|
Sign up to set email alerts
|

Stable Regulation of Cell Cycle Events in Mycobacteria: Insights From Inherently Heterogeneous Bacterial Populations

Abstract: Model bacteria, such as E. coli and B. subtilis, tightly regulate cell cycle progression to achieve consistent cell size distributions and replication dynamics. Many of the hallmark features of these model bacteria, including lateral cell wall elongation and symmetric growth and division, do not occur in mycobacteria. Instead, mycobacterial growth is characterized by asymmetric polar growth and division. This innate asymmetry creates unequal birth sizes and growth rates for daughter cells with each division, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 100 publications
1
25
0
Order By: Relevance
“…S1 ). This inherent heterogeneity is consistent with the variable nature of Mtb, which on the single-cell level exhibits heterogeneity through asymmetric growth and division, differential drug susceptibility, and metabolic state ( 14 18 ). Cell-to-cell variation is most apparent in the ability of Mtb bacilli to take up stains.…”
Section: Resultssupporting
confidence: 71%
“…S1 ). This inherent heterogeneity is consistent with the variable nature of Mtb, which on the single-cell level exhibits heterogeneity through asymmetric growth and division, differential drug susceptibility, and metabolic state ( 14 18 ). Cell-to-cell variation is most apparent in the ability of Mtb bacilli to take up stains.…”
Section: Resultssupporting
confidence: 71%
“…TB is a complex disease that is highly heterogeneous with regards to outcomes of infection, pathology and nature of bacterial populations (Cadena et al, 2017; Logsdon and Aldridge, 2018; Rego et al, 2017). In fact, the apparent static, non-replicating population that persists in chronically infected mice consists of a mixture of heterogeneous populations of replicating, non-replicating but alive, and dead bacteria (Gill et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…With respect o M. tuberculosis, it should be pointed out that recent studies have indicated a high variability in the individual cells' proliferation and growth rates even within a population of a uniform strain culture [12][13][14]. This may induce deviations from the conventional behavior of bacterial growth curves, which normally include the lag-phase, the exponential growth phase, the saturation phase, and the decay phase, and, with respect to two intermediate phases in the aforementioned list, be modeled by the classic population growth models like Verhulst, Gompertz, Richards, etc.…”
Section: Discussionmentioning
confidence: 99%
“…They represent four possible combinations of initial conditions for the mycobacterial cultures: two different initial dilutions determined the initial population density (found optically before placing the culture into the microplate kit) and two different generations cultured previously. To avoid possible bias, the data presented in Columns 1-8, [9][10][11][12][13][14][15][16], and 17-20 in the Supplementary Data (the sheet "Raw data"), and referred to as "sample #" in the plots and discussions below, originate from experiments separated by two-month intervals between them; their initial seeds were prepared separately as well. Table 1.…”
Section: Data Descriptionmentioning
confidence: 99%